THE RELATIONSHIP BETWEEN ENVIRONMENTS OF COFFEE HOUSE WITH THE EMOTIONAL STATES AND PLACE ATTACHMENT AMONG YOUNG GENERATION IN KUCHING - LIEW, BING BING (Universiti Malaysia Sarawak (UNIMAS), 2016)
Coffee drinking culture has fast growing in our world. The mushroomed growing number of modern coffee shop happened in Malaysia. It is because the lifestyles change. Businessman’s see the business opportunity, they change the outlook of coffee house to meet the needs of urban populations. The coffee house wasn’t cheap for young generation but young generation willing to pay for it. Young generation purchasing style nowadays is more towards on status consumption. Young generation had been categorised in a materialistic society who still rely on parental financial support. The technological innovations affect the generation Y easily to accept new concepts of products or services. For example, they accept the luxury restaurants or cafés, as a means of self-expression or symbols of their desired lifestyle. In this study, I will analyses the relationship between coffee house environment with customer emotional states and place attachment among young generation in Kuching.